Peran serta Upaya Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Pendidikan Siswa - Muhammad Daffa; Natasya Deswyta Tampubolon; Abdi Adriyan; Yulistra Naomi Sihombing; Imam Adhi Pratama; Veronica Asri Damayanti; Tassya Septiani (EduInovasi: Journal of Basic Educational Studies, 2026)
This article aims to examine the role of school principal leadership in improving the quality of student education. The method used is a descriptive qualitative approach through library research, by analyzing relevant books, scientific journal articles, and previous studies related to principal leadership and educational quality. The results show that the school principal has a strategic role, not only as a leader but also as a manager, motivator, and supervisor who drives teachers, education staff, and students toward better educational outcomes. Several efforts that can be undertaken by the principal include improving teacher competence and professionalism, enhancing the quality of the learning process, developing students’ academic and non-academic achievements, optimizing the management of facilities and infrastructure, managing educational financing effectively, and conducting regular monitoring and evaluation. The study concludes that effective principal leadership is a key determinant in creating a conducive learning environment and improving the overall quality of the school. Without strong leadership, efforts to improve the quality of education cannot run optimally.